Dynamic Characteristics on Single-Tooth Rock Cutting Considering the Change of Extrusion Zone Height - Yanbo Hu; Guofeng Li; Ning Li (Applied Sciences)
To analyze the dynamic characteristics of single-tooth rock-cutting behavior, this paper proposes that the height of the extrusion zone (hc) is not constant and does not equal the cutting depth in real rock-cutting behavior, and introduces a new dynamic cutting model (NDCM). By analyzing the single-tooth rock-cutting process, the concepts of the single cutting process and cutting frequency (fc) are defined. A method for determining fc based on the tangential cutting force (Fct) is also proposed. A series of single-tooth rock-cutting tests were conducted using numerical simulation, and the influence of rake angle (a), cutting speed (v), and cutting depth (h) on fc was analyzed. The geometric difference coefficient (GDC) is introduced in the new dynamic cutting model, defined as the ratio of hc to h. The determination method of GDC and its relationship with cutting parameters are explored from both theoretical and experimental perspectives. The results show that the cutting frequency corresponds to the main frequency of the tangential cutting force. fc is linearly proportional to v and decreases nonlinearly with increasing h, while the rake angle has little effect on cutting frequency within the range of 10–20°. hc exhibits a nonlinear relationship with h: when the cutting depth is small, GDC is close to 1.0; as h increases, GDC gradually decreases and eventually stabilizes, which aligns with experimental findings. The results of this study provide valuable insights for engineers to better understand the dynamic characteristics of tool–rock interaction in single-tooth rock cutting and offer new perspectives for applying cutting force and optimizing rock-cutting models.